THE TEACHING OF SPEAKING TROUGHT ROLE PLAY AT SMPN 1 MALANG - Sulistyahadi Sulistyahadi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2017)
This study focused on the instructional activities conducted by the teacher in teaching speaking through Role Play at SMPN 1 Malang. The study is a qualitative study, which is designed to obtain information concerning the current status of phenomena (Ary, 2010:29). It tries to describe some important events that occur naturally in the classroom. The study showed that the first step the teacher give leading question to the students. These questions were very important to make the students recall their prior knowledge related to the topic. Therefore, the teacher could bring the students background knowledge from their experience in the classroom. Then the teacher gave dialogue to the students and asked the students what the conversation was about. The second was giving and drilling the examples of expressions to the students. In this part, the teacher drilled the students based on the examples of the expression provided to make the students familiar and pronounce those expressions correctly. Next, the teacher gave tasks to the students to do role play. The procedures to do it are: firstly, the teacher grouped the students into three groups. Each group consisted of ten students. Groups are formed randomly through drawing rolls of paper with the number of one to three. The students who get the same number belong to the same group. Secondly, after the groups of ten students were formed, they decide themselves the roles which include: one student who is having birthday. Five students play role as sellers in public places. Four students prepare a surprising party. The groups are given time to design the script of conversation regarding with the topic which includes the expression explained by the teacher. Thirdly, within a week the students were allowed to consult the draft of the script with the teacher concerning with the content, grammar, and language focus explained by the teacher.